2013
DOI: 10.1016/j.carbpol.2013.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Anionic carbohydrate-containing chitosan scaffolds for bone regeneration

Abstract: Scaffolds derived from naturally occurring polysaccharides have attracted significant interest in bone tissue engineering due to their excellent biocompatibility and hydrophilic nature favorable for cell attachment. In this study, we developed composite chitosan (CH) scaffolds containing anionic carbohydrate, such as chondroitin 4-sulfate (CS) or alginate (AG), with biomimetic apatite layer on their surfaces, and investigate their capacity to deliver progenitor cells (bone marrow stromal cells, BMSC) and model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 49 publications
4
44
0
1
Order By: Relevance
“…We previously developed a biomimetic process to create apatite layers on various biomaterial surfaces, and the created apatite provided a favorable substrate for cell adhesion and osteogenic differentiation. 20,[22][23][24] This study showed that loaded BMP-2 and phenamil were slowly released in a sustainable manner with approximately 7% and 29% of initial burst from scaffolds, respectively. The observed sustained release of BMP-2 can be attributed to increased electrostatic interaction between BMP-2 and charged binding sites on the apatite surface.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…We previously developed a biomimetic process to create apatite layers on various biomaterial surfaces, and the created apatite provided a favorable substrate for cell adhesion and osteogenic differentiation. 20,[22][23][24] This study showed that loaded BMP-2 and phenamil were slowly released in a sustainable manner with approximately 7% and 29% of initial burst from scaffolds, respectively. The observed sustained release of BMP-2 can be attributed to increased electrostatic interaction between BMP-2 and charged binding sites on the apatite surface.…”
Section: Discussionmentioning
confidence: 72%
“…20,22 Briefly, simulated body fluids (SBF) were prepared by sequentially dissolving CaCl 2 , MgCl 2 $6H 2 O, NaHCO 3 , and K 2 HPO 4 $3H 2 O into ddH 2 O. The solution was adjusted to pH 6.0 and then Na 2 SO 4 , KCl, and NaCl were added.…”
Section: Biomimetic Apatite Coating Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Chitosan consists of b-(1,4)-linked D-glucosamine units with variable degrees of N-acetylation (Casettari et al, 2012). It has been used for tissue regeneration (Ma et al, 2010;Cooper et al, 2011;Park et al, 2013) and drug delivery applications (Rokhade et al, 2007;Abruzzo et al, 2012;Ferrari et al, 2013) because of its tissue compatibility, biodegradability and low toxicity (Ao et al, 2011;Cooper et al, 2011;Tsai et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Por apresentarem essas propriedades, são utilizados em aplicações médicas (PETRULYTE;; PETRULIS, 2011;; MEDINE et al, 2012).…”
Section: Biomateriaisunclassified